Pediatric Burn Treatment with Non-Thermal Atmospheric Plasma and Epifast®: Clinical Results - Pablo Rodríguez-Ferreyra; Régulo López-Callejas; Teresa Narváez-Robles; Benjamín Gonzalo Rodríguez-Méndez; Omar Israel Gayosso-Cerón; Antonio Mercado-Cabrera; Irene Lule-Reyna; Othoniel Mondragón-Dagio; Raúl Valencia-Alvarado; Jesús Duarte-Mote (European Burn Journal)
The effective treatment of severe burns in pediatric patients is essential for minimizing complications and promoting optimal recovery. This study investigates the use of non-thermal atmospheric pressure plasma (NTAPP) as an adjuvant therapy in combination with Epifast® for the experimental group, compared to standard care involving early excisions and Epifast® for the control group. A randomized controlled trial was conducted with 40 pediatric patients suffering from superficial partial-thickness and deep dermal burns. The experimental group that received NTAPP daily demonstrated a significant reduction in the need for skin grafts, requiring only 10% compared to 40% in the control group (p = 0.02). Although there were no statistically significant differences in the length of hospital stay, the experimental group showed a trend toward shorter stays (9.85 days vs. 11.65 days; p = 0.38) and lower analgesic consumption (13.01 doses vs. 21.15 doses; p = 0.09). Additionally, the infection rate in the NTAPP-treated group was significantly lower at 25%, compared to 37.95% in the control group (p < 0.05). These findings suggest that NTAPP enhances wound healing while reducing surgical morbidity and the risk of infections. In conclusion, this study highlights the transformative potential of NTAPP as an innovative strategy in pediatric burn management. It combines clinical efficacy with a less invasive approach, representing a significant advance in regenerative medicine and opening new avenues for research into advanced therapies.